Hurler syndrome: Etiology, manifestations, and life complications: A case report (Indian Journal of Case Reports, 2024)
Hurler syndrome is a rare genetic lysosomal storage disorder with a wide range of manifestations and complications ranging from musculoskeletal deformities to cardiac and corneal problems. The life expectancy of diagnosed patients does not usually exceed 10 years of age due to the associated cardiac problems. However, depending on the complication presented, some treatment modalities are offered to enhance the quality of life for these patients. Our case report reviews a case of a set of twins diagnosed with the syndrome, who have undergone bilateral coronoidectomy via a coronal approach. This approach was taken due to the superior extension of the coronoid processes into the infratemporal fossae bilaterally, their low zygomatic arches, and the severely limited mouth opening associated with coronoid hyperplasia. A coronal approach that included a bilateral coronoidectomy with the removal of internal exophytic bone on the zygomatic arch, along with manipulation under sedation and further physiotherapy/OraStretch device was used to reach the final maximum mouth opening of 35 mm for both patients.